2022
DOI: 10.1017/s2045796022000622
|View full text |Cite
|
Sign up to set email alerts
|

Indirect social contact interventions to reduce mental health-related stigma in low- and middle-income countries: systematic review

Abstract: Aims Mental health-related stigma and discrimination are a complex and widespread issue with negative effects on numerous aspects of life of people with lived experience of mental health conditions. Research shows that social contact is the best evidence-based intervention to reduce stigma. Within the context of a rapid development of remote technology, and COVID-19-related restrictions for face-to-face contact, the aim of this paper is to categorise, compare and define indirect social contact (ISC) inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…These formats included text-based messages, videos, theater performances, and combinations of multiple materials. Relevant literature reviews showed comparable destigmatizing effects across formats (Makhmud et al, 2022;Maunder & White, 2019;Naslund & Deng, 2021). However, it remains unclear whether the message format plays a role in achieving intended stigma reduction goals in public mental illness disclosures on social media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These formats included text-based messages, videos, theater performances, and combinations of multiple materials. Relevant literature reviews showed comparable destigmatizing effects across formats (Makhmud et al, 2022;Maunder & White, 2019;Naslund & Deng, 2021). However, it remains unclear whether the message format plays a role in achieving intended stigma reduction goals in public mental illness disclosures on social media.…”
Section: Discussionmentioning
confidence: 99%
“…These typically involve the use of video or audio narratives of people with lived experience of mental illness (Zhuang & Guidry, 2022). Others involve activities such as reading a vignette depicting a person with mental illness and imagining the desired level of contact with them (Makhmud et al, 2022; White et al, 2021).…”
mentioning
confidence: 99%
“…Though this type of direct (i.e., live, face‐to‐face) social contact intervention may help to reduce stigma in health care, 13 it can be challenging to implement as a live face‐to‐face activity due to timing, space, ability to scale up to larger groups, and logistical concerns 14 . Indirect social contact interventions such as viewing of online videos, films, or pre‐recorded narratives (including PhotoVoice [https://photovoice.org/]) depicting lived experience with mental illness have been associated with reductions in stigma among health care providers 13,15,16 …”
Section: Introductionmentioning
confidence: 99%
“…14 Indirect social contact interventions such as viewing of online videos, films, or pre-recorded narratives (including PhotoVoice [https:// photovoice.org/]) depicting lived experience with mental illness have been associated with reductions in stigma among health care providers. 13,15,16 SNAP the Stigma (SNAP) is an engagement and awareness website to de-stigmatize and humanize mental illness. 17 SNAP was created by researchers at a midwestern university to encourage the sharing of lived experiences through PhotoVoice, a participatoryaction method in which participants capture and reflect upon photos of their lived experiences.…”
mentioning
confidence: 99%
“…The influential meta‐analysis by Corrigan and colleagues and other systematic reviews 9–12 revealed that interventions for mental health‐related public stigma reduction have small to moderate immediate effect sizes. Also, factors such as cultural and social norms, as well as support for public policies related to mental illness, are important to consider in efforts to reduce public stigma 1,9,13 . Several countries have previously launched public anti‐stigma campaigns.…”
Section: Introductionmentioning
confidence: 99%